Epidemiology and Pathogenesis of COVID-19, a Pandemic Novel Coronavirus Disease; Review from Global Perspectives - Adhikari, N.P.; Adhikari, S; Karki, S; Paudel, G; Sharma, B.P. (Nepalese Veterinary Journal, 2023)
Available within the full article